(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objective: To assess the prevalence of Extended spectrum beta lactamase (ESBL) and Metallo beta lactamase (MBL) producing Pseudomonas aeruginosa from pus samples. Methods: A cross-sectional study was conducted at Kanti Children’s Hospital, Kathmandu, Nepal during which 316 pus samples were collected and tested using standard microbiological procedures. Antibiotic Susceptibility Test (AST) was done by Kirby-Bauer disk diffusion method and the detection of ESBL and MBL production were done using Ceftazidime/clavulanic acid combined disk test and Imipenem- Ethylenenediaminetetraacetic acid combined disk test respectively as per CLSI guideline 2014. Results: The prevalence rate of P. aeruginosa was found to be 7.9% in pus samples. Out of 25 P. aeruginosa isolates 9(36%) were ESBL producers and 2(8%) were MBL producers. ESBL producers were predominant in the age group 2-3 years (33.3%) and in male patient (55.6%). Out of 2 MBL producing P. aeruginosa, 1(50%)was isolated from the age group below 2 years and male patient and 1(50%) from the age group 8-9 years and female patient. 96% of isolates showed sensitive to Polymyxin B. Conclusion: The study showed increasing trend of ESBL and MBL production in P. aeruginosa so constant survey of prevalence of ESBL and MBL producing isolates is essential to control and manage spread of these isolates in different units of health institutions.